Accounting in the Hotel and Catering Industry / Fourth Edition - Harris Peter; Hazzard A. Peter (Stanley Thornes (Publishers) Ltd, 1994)
This book covers the fundamental book-keeping and accounting principles and their application in the hotel and catering industry. Preface, Introduction, Recording of Cash, Recording of Expenditure, Recording of Salaries and Wages, Recording of Income, Value Added Tax, Trial Balance, Preparation of Final Accounts, Accounting Adjustments - Routine and Year End, Depreciation and Replacement and Disposal of Fixed Assets, Incomplete Records, Accounts of Non-Profit-Making Organizations, Accounts of Parthnerships, Accounts of Limited Companies, Departmental Accounting, Cost-Volume-Profit Relationships, Introduction to Budgetary Control, Index, Context of Managerial Accounting in the Hotel and Catering Industry.